GC-Mass Spectrometry Analysis of Iraqi Moringa Oleifera Seeds Extract - Fiham Jassim AL-Obaidi1, Abid A. Thaker2 , Asmiet Ramizy3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Moringa oleifera is an important traditional medicinal plant usedfor the treatment of many health problems.It is widely cultivated across the world but it has not well known orwell-studied in Iraq. Therefore, the aimof this study is to identify the bioactive compounds present in acetone:methanol (1:1) seeds extractof IraqiMoringa olieifera by using GC-Mass Spectrophotometry.The results of this analysis revealed 41 compounds which include ,terpenes ( cis-beta-Ocimene 0.97%,Cedrene 0.20%, Cedrenol 1.40%, Verrucarol 0.29 , Dehydroxy-isocalamendiol 0.09% , beta-Myrcene0.14% , 3-Thujene 0.06%, Ocimene 0.72% , Sabinene 0.37% Aromadendrene 1.54%) , phenols (0.34%,Eugenol 0.49%, cis-Isoeugenol 1.21%, Methoxyeugenol 0.26%, Ferrocene 0.57%, Phenol, 2-methoxy-4-(1-propenyl)-, (Z) 0.34 , Oxabicyclo[3.3.0]octan-2-one -7-neopentylidene) 0.61% ) , fatty acid methyl esters( n-Tridecanoic acid 0.15% , Undecanoic acid 0.09% , Pentadecanoic acid 34.43%, 4-Hexadienal 1.52% ,Dodecanoic acid 11.02% , cis-Vaccenic acid 21.39%, Hexadecenoic acid 0.15% , Eicosanoic acid 0.03%), acid(myristicin,7.8%), Phenyl propanoid (Asarone, 4.99%), Antioxidant (-tert-Butyl-4-hydroxyanisole, 1.38%),Drug (Berbine, 2,3,9,10-tetramethoxy, 0.73%), Drug (Thiazolo, 0.63%), aldehyde (Trimethylsilyl vanillin,0.61%), hormone (Octenoic acid, 0.46%), Amine (ethyl ester, 0.42%), Carboxylic acid (Dimethylandrost5-en-3-one, 0.28%), Terpenoid (Lavandulol, 0.19%), Heterocyclic compound (Buten-3-one, 1-(2-carboxy4,4-dimethylcyclobutenyl, 0.18%), Volatile oil (Butanoic acid, 0.16%), Fatty alcohol (1-Heptatriacontanol,0.12%), Hydroxy carbon-alkene-(Carene, 0.11%).It can be concluded from this study that the seeds are considered a rich source of bioactive compounds.